2003
DOI: 10.1186/bcr753
|View full text |Cite
|
Sign up to set email alerts
|

Involution of the mouse mammary gland is associated with an immune cascade and an acute-phase response, involving LBP, CD14 and STAT3

Abstract: The mouse mammary gland is an excellent model system with which to study both the regulation of development and the functional differentiation of an organ. Most of the development occurs postnatally, when the gland undergoes a highly regulated cascade of invasive growth, branching, differentiation, secretion, apoptosis and remodelling during each pregnancy cycle [1,2]. Terminal differentiation of the alveolar epithelium is completed at the end of gestation with the onset of milk secretion (lactation). APR = ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
194
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(212 citation statements)
references
References 61 publications
(46 reference statements)
14
194
1
1
Order By: Relevance
“…In this process, the remaining MFGs are also cleared from the gland (8). The involution process is regulated at the transcriptional level and is associated with the up-or down-regulation of a set of genes (26,27). In this report, we showed that the MFG-E8 gene was strongly expressed in the mammary gland during the lactation and involution periods.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this process, the remaining MFGs are also cleared from the gland (8). The involution process is regulated at the transcriptional level and is associated with the up-or down-regulation of a set of genes (26,27). In this report, we showed that the MFG-E8 gene was strongly expressed in the mammary gland during the lactation and involution periods.…”
Section: Discussionmentioning
confidence: 57%
“…However, our mice were maintained in specific pathogen-free conditions, and mastitis was never found in the WT mice, suggesting that the mastitis in the MFG-E8 Ϫ/Ϫ mice was induced without bacterial infection. The involution of the mammary gland is regulated by the STAT3 transcription factor (31,32) and is accompanied by the activation of various inflammatory genes such as CXCL1 and CXCL10 (27), which recruit inflammatory cells into the mammary gland. It is possible that the prolonged involution process in MFG-E8 Ϫ/Ϫ mice causes the extended activation of inflammatory genes, leading to severe inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Using microarray analysis, Stein et al identified a set of genes specifically upregulated during the initial 4 days of involution (54). Further analysis of gene function revealed a set of genes associated with a wound-healing response, specifically neutrophil and macrophage activation.…”
Section: Involutionmentioning
confidence: 99%
“…Following pregnancy and lactation, the alveolar mammary epithelium (which produces milk during lactation) undergoes widespread synchronized apoptosis, removing up to 90% of the mammary epithelium within only 7–10 days. This involution process returns the mammary epithelium to a quiescent state capable of future rounds of alveolar budding and pregnancy-induced expansion [3, 4] . While the mammary gland represents a rather dramatic example of physiological cell death, most tissues harbor some level of cell death at any given time.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of cytokine and chemokine production is mediated by macrophages, with these cytokines and chemokines instructing the response of the cells in the adaptive immune system. Efferocytosis is critical to macrophage-mediated suppression of adaptive immune responses and resolution of inflammation [4, 6] . Efferocytosis resembles other categories of phagocytosis in many ways.…”
Section: Introductionmentioning
confidence: 99%